185k views
2 votes
The graph of
f(x) = (1)/(4) 3^(x) -6 is shown below. g(x) is a transformation of f(x). How would you write the equation for the function g(x)?

A.
g(x) = (1)/(4)3^(x) +2
B.
g(x) = -(1)/(4)3^(x) -6
C.
g(x) = (1)/(3) *4^(x) +3
D.
g(x) = 3^(x) +2

The graph of f(x) = (1)/(4) 3^(x) -6 is shown below. g(x) is a transformation of f-example-1
User TheLuminor
by
5.6k points

2 Answers

4 votes

Answer:

the answer would be like finding the point and then doing the math

after the math u will find you answer on the am going to say either C or D

Explanation:

User APugLife
by
5.5k points
4 votes

Answer:

A

Explanation:

If g(x) is a transformation of f(x), then we can consider function f(x) as parent function.

So, to get the graph of the function g(x), we have to translate the graph of the function f(x) 8 units up.

This translation will give us the function


g(x)=f(x)+9\\ \\g(x)=(1)/(4)\cdot 3^x-6+8\\ \\g(x)=(1)/(4)\cdot 3^x+2

The graph of f(x) = (1)/(4) 3^(x) -6 is shown below. g(x) is a transformation of f-example-1
User Gerben Jacobs
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.